The Role of Transformational Leadership in Facing the Challenges of Organizational Change - Thalia Anandani; Nuri Aslami (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
Organizational change is an inevitable phenomenon in a dynamic business environment. Transformational leadership has an important role in dealing with the challenges that arise during the organizational change process. This study aims to investigate the role of transformational leadership in overcoming the challenges of organizational change and its impact on organizational performance. The research method used is a literature study that involves an in-depth analysis of relevant previous research. The results of the analysis show that transformational leadership plays a key role in influencing the attitudes and behaviors of organizational members during change. Transformational leadership is able to motivate and inspire organizational members to adapt to change, overcome uncertainty, and improve performance. Factors such as effective communication, strong team building, and individual skill development also influence the effectiveness of transformational leadership in meeting the challenges of organizational change. This research provides valuable insights for leaders and managers in understanding the role of transformational leadership in managing organizational change successfully.